Timing resistance training programming the muscle clock for optimal performance - Ashmore, Amy 1971- (Human Kinetics, 2020)
Timing Resistance Training goes beyond periodization to guide readers through the premise of muscle clocks and how those clocks can be manipulated to control and improve muscle performance